High-Quality, InN-Based, Saturable Absorbers for Ultrafast Laser Development - Laura Monroy; Marco Jiménez-Rodríguez; Eva Monroy; Miguel González-Herráez; Fernando B. Naranjo (Applied Sciences, 2020)
New fabrication methods are strongly demanded for the development of thin-film saturable absorbers with improved optical properties (absorption band, modulation depth, nonlinear optical response). In this sense, we investigate the performance of indium nitride (InN) epitaxial layers with low residual carrier concentration (<1018 cm−3), which results in improved performance at telecom wavelengths (1560 nm). These materials have demonstrated a huge modulation depth of 23% and a saturation fluence of 830 µJ/cm2, and a large saturable absorption around −3 × 104 cm/GW has been observed, attaining an enhanced, nonlinear change in transmittance. We have studied the use of such InN layers as semiconductor saturable absorber mirrors (SESAMs) for an erbium (Er)-doped fiber laser to perform mode-locking generation at 1560 nm. We demonstrate highly stable, ultrashort (134 fs) pulses with an energy of up to 5.6 nJ.